The effect of different oral hygiene regimens on the quantity of cariogenic plaque on orthodontic bands with different attachments (A clinical photographic study) - Enas J Almusawi; Hayder F Saloom (College of Dentistry/ University of Baghdad, 2014)
Background: Fixed orthodontic appliances impede the maintenance of oral hygiene and result in plaque accumulation leads to enamel demineralization caused by acids produced by bacteria. Studies on plaque control strategies in orthodontic populations are limited. This might be caused by difficulties in the quantitative evaluation of dental plaque because the teeth have various levels of bracket coverage, and different tooth sizes and malocclusions, making the traditional categorical indices complex. The present study aims to evaluate the effect of different hygiene protocols on plaque quantity on bands with different attachments. Materials and method: Twenty patients had four bands within the orthodontic appliance. Then randomly divided into four groups of hygiene regimens where group A used chlorhexidine dentifrice, group B used fluoridated dentifrice, group C used chlorhexidine mouthwash along with chlorhexidine dentifrice and group D used chlorhexidine mouthwash in addition to the fluoride dentifrice. Bands were removed four weeks after the appliance been in place, cut out carefully into 2 pieces from the center of the mesial and distal contact areas, biochemical test (clinprocario L-pop) was applied then 80 digital photographs were obtained. Four areas of interest were estimated which are mesially and distally to each attachment (2 mm) in width each. Percentage of plaque in these areas was calculated and statistically analyzed. Results: Side difference revealed that the plaque accumulated on the right sided bands more than the left, however the difference was not significant. It was also found that the lower bands had insignificantly higher amount of plaque than the upper ones. Conclusions: The four groups of oral hygiene regimens have no significant different effects on the plaque amount. Moreover, the oral hygiene maintenance is more difficult in the right side than the left side but the difference was not significant. The lower arch accumulated insignificantly more plaque than the upper. Also, difference in attachments has no influence on plaque amount.